2020
DOI: 10.31083/j.rcm.2020.02.68
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis after TAVI: a meta-analysis and systematic review of epidemiology, risk factors and clinical consequences

Abstract: Infective endocarditis (IE) represents one of the most challenging clinical entities, requiring a multidisciplinary approach. The increasing number of surgical and transcatheter heart valves replacements performed annually lead to a higher incidence of prosthetic valve endocarditis. Transcatheter aortic valve implantation (TAVI) brought a new alternative for the treatment of aortic stenosis and a new subgroup of IE with its features. We aimed to compare the incidence of IE in TAVI and surgical valve replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Most frequently isolated causative organisms are gram-positive bacteria such as streptococcus (25.3%), staphylococci (25.3%), and enterococci (24.1%), with Enterococcus spp. as a leading cause in patients who had undergone the transfemoral catheter route [ 9 ]. The all-cause mortality of post-TAVI-IE has been reported to be as considerable at 75% one year after diagnosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most frequently isolated causative organisms are gram-positive bacteria such as streptococcus (25.3%), staphylococci (25.3%), and enterococci (24.1%), with Enterococcus spp. as a leading cause in patients who had undergone the transfemoral catheter route [ 9 ]. The all-cause mortality of post-TAVI-IE has been reported to be as considerable at 75% one year after diagnosis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of post-TAVI-IE and the following septic embolic stroke is a challenging medical dilemma. Persistent infection, uncontrolled embolism, or refractory heart failure may indicate an open-heart surgery [ 5 , 9 ], which was initially avoided in this group of patients who are deemed at high risk to undergo an operation. Therefore, despite having met indications for open-heart surgery, most patients were managed conservatively with antibiotics [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common microorganisms known to cause TAVR-IE are gram-positive cocci, which include Staphylococcus aureus, coagulase negative staphylococci, and enterococci [ 1 – 3 , 6 , 16 18 ]. Streptococcus has also been reported to be an important cause of TAVR-IE [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis and systematic review of infective endocarditis after transcatheter aortic valve repair showed 38% overall mortality [ 23 ]. Autologous vascular grafts offer a natural resistance to infection, but, even with silver or antibiotic coatings, the incidence of Dacron graft infection is reported to be between 0.5% and 6% (depending on the operation, location, and stage of atherosclerosis), with up to 75% mortality and up to 70% limb amputation rates [ 3 , 24 ].…”
Section: Endocarditis In Patients With Prosthetic Heart Valves (Phv)mentioning
confidence: 99%